Monochloramine Loss Mechanisms in Tap Water: Zhang et al. (1st November 2017) - Zhang, Qianyi; Davies, Evan G. R.; Bolton, James; Liu, Yang
ABSTRACT: : Chloramination has been widely applied for drinking water disinfection, with monochloramine (NH2 Cl) the dominant chloramine species. However, under neutral pH, NH2 Cl can autodecompose and react with chemical components in drinking water, thus decreasing disinfection efficiency. In tap water, the NH2 Cl loss rate can be influenced by temperature, pH, Cl/N molar ratio, the initial NH2 Cl concentration, and the natural organic matter (NOM) concentration. A good prediction of NH2 Cl loss can assist in the operation of drinking water treatment plants. In this research, a kinetic rate constant )and a reactive site fraction (S = 0.43 ± 0.06) for the reaction between free chlorine released from NH2 Cl autodecoposition and tap water NOM were derived from a kinetic model to predict the NH2 Cl loss under various conditions. A temperature‐dependent model was also developed. The model predictions match well with the experimental results, which demonstrates the validity of the model and provides a convenient and accurate method for NH2 Cl loss calculations.